Backlash in global health and the end of AIDS' exceptionalism in Brazil, 2007–2019. Issue 6 (3rd June 2022) - Cueto, Marcos; Lopes, Gabriel
ABSTRACT: This paper examines the decline of the AIDS Programme in Brazil, the Latin American country most affected by the epidemic, with emphasis in the second decade of the twenty-first century. For many years, Brazil served as a model in Global Health due to a comprehensive preventive policy, a partnership between the government and health activists and the support of life-saving drugs as public goods rather than commodities. The regression of AIDS policies in Brazil interacted with developments in the United States as well as with multilateral agencies like UNAIDS that emphasised biomedicalisation in the response to the disease where broad human-rights programmes and alliance with activists were not priorities. International programmes like the 'Ending AIDS' campaign indirectly undermined the exceptional status AIDS enjoyed since the late 1980s. The backlash in Brazilian policies to fight AIDS was a result of the fragmentation of the left and the empowerment of radical conservative authoritarian and religious forces. The result was the breakdown of the long-held belief that successful anti-AIDS disease programmes could simultaneously help control the disease and build better healthcare systems and ultimately prompted the end of the special place AIDS' policy had in Brazil.